Hepatitis B virus replication - Beck, Juergen (Baishideng Publishing Group Co., Limited, 2007)
Hepadnaviruses, including human hepatitis B virus (HBV), replicate through reverse transcription of an RNA intermediate, the pregenomic RNA (pgRNA). Despite this kinship to retroviruses, there are fundamental differences beyond the fact that hepadnavirions contain DNA instead of RNA. Most peculiar is the initiation of reverse transcription: it occurs by protein-priming, is strictly committed to using an RNA hairpin on the pgRNA, ε, as template, and depends on cellular chaperones; moreover, proper replication can apparently occur only in the specialized environment of intact nucleocapsids. This complexity has hampered an in-depth mechanistic understanding. The recent successful reconstitution in the test tube of active replication initiation complexes from purified components, for duck HBV (DHBV), now allows for the analysis of the biochemistry of hepadnaviral replication at the molecular level. Here we review the current state of knowledge at all steps of the hepadnaviral genome replication cycle, with emphasis on new insights that turned up by the use of such cell-free systems. At this time, they can, unfortunately, not be complemented by three-dimensional structural information on the involved components. However, at least for the ε RNA element such information is emerging, raising expectations that combining biophysics with biochemistry and genetics will soon provide a powerful integrated approach for solving the many outstanding questions. The ultimate, though most challenging goal, will be to visualize the hepadnaviral reverse transcriptase in the act of synthesizing DNA, which will also have strong implications for drug development.